Rancang Bangun Sistem Informasi Dewan Guru Besar Universitas Halu Oleo - Anshari Nur, Muh Nadzirin; Galugu, Indrayati; Lolok, Agustinus (UNIVERSITAS RAHARJA, 2023)
the accreditation and ranking of tertiary institutions, institutionally Halu Oleo University already has a Professors Council organization as a forum that oversees professors at Halu Oleo University, in the process an institution or organization should have an information media and publication of organizational activities but currently the professorship council of Halu Oleo University does not yet have the media. The purpose of this research is to design an information system that contains all institutional aspects of the professorial council of Halu Oleo University including board profile information professors, database of professors at Halu Oleo University, activity agendas, information on professor inauguration activities, announcements, documentation both in the form of photos and videos as well as some other information that helps the community and external parties to get to know more closely at the Halu Oleo University professorial council organization. The method used in this study is the information system design method with the waterfall model, the research starts from the method of analysis, design, implementation, testing, development and maintenance. The outputs resulting from this research are information system products that can be accessed online, databases and directories. professors at Halu Oleo University, the test results show that the information system can run well.